Game modding: A design cognitive perspective in entrepreneurship education (Journal of Applied Learning and Teaching, 2025)
This design-based research investigates how game modding—intentional alterations to a game’s original content—can foster a cognitive approach to design thinking among business students, grounded in constructionist theory. A two-stage game-based activity was created and implemented in a Business Game class at a specialized entrepreneurship college in São Paulo, Brazil. Data collection included video recordings, interviews, and student reports. The analysis focused on a representative group of four students, examining the design cognitive processes employed during their redesign journey. Our analysis reveals that due to the absence of a repertoire of previous design solutions, the students grounded their analogies in their own sociocultural context, reflecting their social norms, and through interdisciplinary thought processes. To address the research question, ‘How can game modding support the development of business students’ cognitive perspective in design?’ we propose that game modding serves as a useful pedagogical tool to foster essential cognitive processes in design thinking, particularly within a business education context. Game modding helps develop business students’ cognitive perspective by creating an experiential learning environment emulating the entrepreneurial journey.